2019
DOI: 10.1002/pip.3096
|View full text |Cite
|
Sign up to set email alerts
|

Bandgap engineered smart three‐terminal solar cell: New perspectives towards very high efficiencies in the silicon world

Abstract: We present the design of a new architecture of three-terminal (3-T) photovoltaic tandem solar cells. It combines an interdigitated back contacted (IBC) bottom lateral subcell with a heterojunction vertical top cell. In this concept, the two subcells can work independently and there is no need for tunnel junctions. It is particularly well suited to silicon back contact subcells and to various types of top cell materials from III-V compounds or perovskites. The working principle is detailed here using as an exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 36 publications
(42 reference statements)
0
21
0
Order By: Relevance
“…for the limiting case (which cannot be achieved in real world devices). At this point the two subcells become independent from each other, representing the ideal theoretical case as also discussed elsewhere [34]. Thus it can be concluded that during device fabrication utmost attention on designing this shared contact to be very lowly resistive as well as on choosing appropriate wafer material are crucial to minimize the mutual dependence of the subcells' J-V-characteristics.…”
Section: Ltspice Equivalent Circuit Simulationsmentioning
confidence: 81%
See 2 more Smart Citations
“…for the limiting case (which cannot be achieved in real world devices). At this point the two subcells become independent from each other, representing the ideal theoretical case as also discussed elsewhere [34]. Thus it can be concluded that during device fabrication utmost attention on designing this shared contact to be very lowly resistive as well as on choosing appropriate wafer material are crucial to minimize the mutual dependence of the subcells' J-V-characteristics.…”
Section: Ltspice Equivalent Circuit Simulationsmentioning
confidence: 81%
“…In order to reach sufficient electron selectivity between the two subcells in a tandem device, the ETL adjacent to the perovskite must create an asymmetric energetic barrier [34] (see Figure 6a and b): The conduction band only experiences a small band offset, thus allowing electrons to pass [55] while holes are blocked by the considerable energetic barrier in the valence band. The simulated solar cell parameters for both subcells when set to MPP conditions in the IBC 3T configuration are included in Table S4.…”
Section: Verification Of Efficient Charge Transport In Ibc 3t Devices...mentioning
confidence: 99%
See 1 more Smart Citation
“…This study considers a novel 3T device architecture, which features a carrier selective band offset barrier, [ 3 ] delivering 3T tandem efficiencies without the need for lateral transport layers, which contribute to parasitic absorption losses. In addition, the design eliminates the need for grid alignment to minimize shading that is a constraint in 4T designs.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 ] This study reports on the development of a novel device, the selective band offset three‐terminal tandem that presents advantages over existing designs, which has been experimentally demonstrated by two groups. [ 2,3 ]…”
Section: Introductionmentioning
confidence: 99%